Selective glycinergic input from vGluT3 amacrine cells confers a suppressed‐by‐contrast trigger feature in a subtype of M1 ipRGCs in the mouse retina. (17th August 2021) - Lee, Seunghoon; Chen, Minggang; Shi, Yuelin; Zhou, Z. Jimmy
Abstract : Key points: M1 intrinsically photosensitive retinal ganglion cells (ipRGCs) are known to encode absolute light intensity (irradiance) for non‐image‐forming visual functions (subconscious vision), such as circadian photoentrainment and the pupillary light reflex. It remains unclear how M1 cells respond to relative light intensity (contrast) and patterned visual signals. The present study identified a special form of contrast sensitivity (suppressed‐by‐contrast) in M1 cells, suggesting a role of patterned visual signals in regulating non‐image‐forming vision and a potential role of M1 ipRGCs in encoding image‐forming visual cues. The study also uncovered a synaptic mechanism and a retinal circuit mediated by vesicular glutamate transporter 3 (vGluT3) amacrine cells that underlie the suppressed‐by‐contrast response of M1 cells. M1 ipRGC subtypes (M1a and M1b) were revealed that are distinguishable based on synaptic connectivity with vGluT3 amacrine cells, receptive field properties, intrinsic photo sensitivity and membrane excitability, and morphological features, suggesting a division of visual tasks among discrete M1 subpopulations. Abstract: The M1 type ipRGC (intrinsically photosensitive retinal ganglion cell) is known to encode ambient light signals for non‐image‐forming visual functions such as circadian photo‐entrainment and the pupillary light reflex. Here, we report that a subpopulation of M1 cells (M1a) in the mouse retina possess the suppressed‐by‐contrast (sbc) trigger feature that is a receptive field property previously found only in ganglion cells mediating image‐forming vision. Using optogenetics and the dual patch clamp technique, we found that vesicular glutamate transporter 3 (vGluT3) (vGluT3) amacrine cells make glycinergic, but not glutamatergic, synapses specifically onto M1a cells. The spatiotemporal and pharmacological properties of visually evoked responses of M1a cells closely matched the receptive field characteristics of vGluT3 cells, suggesting a major role of the vGluT3 amacrine cell input in shaping the sbc trigger feature of M1a cells. We found that the other subpopulation of M1 cells (M1b), which did not receive a direct vGluT3 cell input, lacked the sbc trigger feature, being distinctively different from M1a cells in intrinsic photo responses, membrane excitability, receptive‐field characteristics and morphological features. Together, the results reveal a retinal circuit that uses the sbc trigger feature to regulate irradiance coding and potentially send image‐forming cues to non‐image‐forming visual centres in the brain.